C2.1 Delivery of behavioural interventions for tics in an intensive outpatient format followed by remote delivery: a uk paediatric case series. (4th October 2017) - Taylor, C; Greenhalgh, J; Stark, D; Murphy, T; Heyman, I; McFarlane, F
Abstract : Background: Tourette Syndrome (TS) most commonly develops in childhood 1 and can impact children's daily functioning 2 and quality of life. 3 Randomised controlled trials have established the effectiveness of behavioural therapies for tics, such as Habit Reversal Therapy (HRT) and Exposure and Response Prevention (ERP) in child populations. 4, 5 A lack of providers able to deliver these treatments locally can require families to travel long distances and can cause difficulties in attending weekly face to face appointments. 6 Previous USA case series' provide evidence that intensive outpatient behavioural treatments for tics can result in reduced tic severity, improved functioning and continued treatment satisfaction. 7, 8 In recent years there is emerging evidence for remote delivery of behavioural therapy for tics. 9 This case series aims to establish the feasibility of offering intensive treatment for tics, with the remainder of treatment delivered via telemedicine. Method: Following outpatient assessment and case formulation, children received ERP 10 for tics. Delivery was a combination of intensive treatment (taking place over two consecutive days) followed by weekly remote delivery by telemedicine. The number of telemedicine sessions varied by need (range=2–12; mode=6/7). Measures included tic severity (YGTSS), impact on daily functioning (CGAS), quality of life (GTS-QOL; Peds-QL) and emotional and behavioural problems (SDQ). Results: Significant reductions in tic severity and improvements in children's daily functioning, quality of life and emotional and behavioural difficulties were found post treatment. Conclusion: This is the first paediatric UK case series establishing the efficacy of adapted behaviour treatment for tics, encompassing a broad evaluation of outcome including quality of life. Significant reductions in tic severity and improvements in functioning were comparable to those achieved with weekly treatment 11 and therefore adapted behavioural treatments have the potential to provide effective and welcomed alternatives for families and community services. Clinical implications and suggestions for further research are discussed. References: . R Yates, K Edwards, J King, O Luzon, M Evangeli, D Stark, T Murphy. Habit reversal training and educational group treatments for children with Tourette syndrome: A preliminary randomised control trial. Behaviour Research and Therapy 2016;80:43–50. . EA Storch, CW Lack, LE Simons, GR Geffken. A measure of functional impairment in youth with Tourettes Syndrome. Journal of Pediatric Psychology 2007;32(8):950–959. . D Cutler, T Murphy, J Gilmour, I Heyman. The quality of life of young people with Tourette syndrome. Child: Care, health and development 2009;35(4):496–504. . C Hollis, M Pennant, J Cuenca, C Glazebrook, T Kendall, J Stern. Clinical effectiveness and patient perspectives of different treatment strategies for tics in children and adolescents with Tourette syndrome: A systematic review and qualitative analysis. Health Technology Assessment 2016;20(4):1–450. . N Dutta, AE Cavanna. The effectiveness of habit reversal therapy in the treatment of Tourette syndrome and other chronic tic disorders: A systematic review. Functional Neurology 2013;28(1):7. . J Cuenca, C Glazebrook, T Kendall, T Hedderly, I Heyman, G Jackson, T Murphy C Hollis. Perceptions of treatment for tics among young people with Tourette syndrome and their parents: A mixed methods study. BMC Psychiatry 2015;15(1):46. . TH Blount, AT Lockhart, RV Garcia, JJ Raj, AL Peterson. Intensive outpatient comprehensive behavioural intervention for tics: A case series. World Journal of Clinical Cases 2014;2(10):569–577. . TH Blount, JJ Raj, AI Peterson. Intensive outpatient comprehensive behavioral intervention for tics: A clinical replication series. Cognitive and Behavioural Practice 2017. doi: 10.1016/j.cbpra.2017.02.001 . EJ Ricketts, AR Goetz, MR Capriotti, CC Bauer, NG Brei, DW Woods. A randomized waitlist-controlled pilot trial of voice over Internet protocol-delivered behaviour therapy for youth with chronic tic disorders. Journal of telemedicine and telecare 2015;22(3):153–162. . C Verdellen, J Van De Griendt, A Hartmann, T Murphy, ESSTS Guidelines Group. European clinical guidelines for Tourette syndrome and other tic disorders. Part III: behavioural and psychosocial interventions. European child & adolescent psychiatry 2011;20(4):197–207. . C Whittington, M Pennant, T Kendall, C Glazebrook, P Trayner, M Groom, T Murphy. Practitioner Review: Treatments for Tourette syndrome in children and young peoplea systematic review. Journal of Child Psychology and Psychiatry 2016;57(9):988–1004.